Danish development cooperation experiences in contexts of autocratisation - Adam Moe Fejerskov; Trine Rosengren Pejstrup (Danish Institute for International Studies (DIIS), 2024)
The past decade ushered in an almost historic backslide towards more autocratic forms of governance. Today, for the first time in almost thirty years, the world has more closed autocracies than liberal democracies, and the past two years alone have seen nine new countries move into this category. In the current (geo)political context of democratic backsliding, Denmark will face an expanding collection of situations and countries of autocratisation with which we must engage. This commissioned study has reviewed Danish country- experiences in Burkina Faso, Ethiopia, Mali, Myanmar, Syria, and Uganda, and collated the cross-cutting and collective learnings from them. The cases show a diversity of ways to think about and respond to autocratisation, but they also stress similarities in challenges as to how we collect intelligence and information, analyze local circumstances and developments, and respond to intensified processes of autocratisation, ruptures such as coups, or opposite trajectories of improvement that may be every bit as difficult to respond to in a timely and appropriate manner.
Keywords: 300